Durable and flexible graphene composites based on artists' paint for conductive paper applications. (June 2015) - Mates, Joseph E.; Bayer, Ilker S.; Salerno, Marco; Carroll, Patrick J.; Jiang, Zhenguo; Liu, Lei; Megaridis, Constantine M.
Abstract: An acrylic emulsion artists' paint containing chlorinated copper phthalocyanine pigment was modified with variable-size multilayer graphene (exfoliated graphite) to induce low electrical resistance; composite films were spray-cast on common printing paper, heat-cured, and subsequently polished under mild compression, to produce highly conductive paper. The mechanically robust conductive paint showed excellent adhesion to the underlying paper, as determined by Taber abrasion and tape peel tests, which displayed no adhesive failure under the test conditions studied. The conductivity of the paper substrates were tuned by changing the concentration and the size of the multilayer graphene particles. Detailed conductivity measurements showed stable Ohmic current–voltage behavior. The optimum graphene-in-paint formulations resulted in sheet resistances of the order of 10 Ω/sq. Standard electrostatic force microscopy measurements showed uniform surface electric field gradient distribution strongly correlating with the surface topography. Similarly, scanning Kelvin probe microscopy measurements indicated stable work functions close to 5 eV, comparable to highly-ordered pyrolytic graphite. Furthermore, Kelvin probe measurements were more sensitive to surface charges related to copper phthalocyanine domains, which are known to have semiconducting properties. Finally, the conductive papers were also tested in the 0.50–0.75 terahertz frequency range for electromagnetic interference shielding (EMI) characterization and displayed quasi-metallic shielding performance.